Mercury Ion-Selective Electrode With Self-plasticizing Poly(n-buthylacrylate) Membrane Based On 1,2-Bis-(N '-benzoylthioureido)cyclohexane As Ionophore - Jumal, J; Yamin, BM; Ahmad, M; Heng, LY (Elsevier Science Bv, 2024)
Indexed by WOS